2012
DOI: 10.1165/rcmb.2010-0335oc
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class II and CD9 in Human Eosinophils Localize to Detergent-Resistant Membrane Microdomains

Abstract: Eosinophils function in murine allergic airways inflammation as professional antigen-presenting cells (APCs). In murine professional APC cell types, optimal functioning of MHC Class II depends on its lateral association in plasma membranes and colocalization with the tetraspanin CD9 into detergent-resistant membrane microdomains (DRMs). With human eosinophils, we evaluated the localization of MHC Class II (HLA-DR) to DRMs and the functional significance of such localization. In granulocyte-macrophage colony-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…1 and 5b; ref. 24), as well as cytoplasmic distribution of varied proteins, such as CD63 (ref. 17; Fig.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and 5b; ref. 24), as well as cytoplasmic distribution of varied proteins, such as CD63 (ref. 17; Fig.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…17,24,26) and protein disulfide isomerase (PDI) 27 in leukocytes. We demonstrated that CD9 is abundant on the surface of eosinophil leukocytes, presenting the first EM data of the ultrastructural immunolocalization of CD9 in human eosinophils, which represents a novel insight into the organization of the antigen presentation complex of these cells 24 . The technique has also been applied to the study of molecules involved in the endocytic pathway such as Rab7 and LC3, labeled in phagosomes within macrophages infected with mycobacteria (R.C.N.M., unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD9 is an intracellular and cell surface protein abundant in eosinophils to such an extent as to be considered an eosinophil marker. 49 In fact, CD9 serves as a molecule that delivers stimulation signals on eosinophils. 50 Several authors have found decreasing CD9 expression in eosinophils on activation, a phenomenon probably caused by release/shedding of soluble forms of CD9 and not caused by intracellular degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for CRMM disruption to provide separation of distinct intracellular responses to the same extracellular signal is highlighted by recent studies demonstrating that while the IL-5 receptors localize to both CRMMs and detergent-soluble membrane regions in eosinophils, the localization determines which intracellular signaling proteins are directly associated with the receptor [42], [43]. Lei and colleagues found that IL-5Rs localized to CRMMs co-immunoprecipitate with the membrane-anchored MAPK signaling cascade initiator, Lyn tyrosine kinase.…”
Section: Introductionmentioning
confidence: 99%